Produtividade em diferentes genótipos de soja para enzima urease - Lamonica, Giovana Contarelli (Universidade Federal de São Carlos, 2022)
Plants need nitrogen at all stages of development, which is considered an essential nutrient. Nitrogen can be absorbed from the soil, mainly in the form of inorganic compounds, nitrate, and ammonia. However, urea is an organic nitrogenous compound that plants can also absorb, being hydrolyzed into ammonia and carbon dioxide by the enzyme urease. In soybeans, two main types of urease are found, the ubiquitous urease, present in all plant tissues, and the embryo-specific urease, present in grains and in developing embryos. The objective of this work was to investigate possible changes in the growth and yield of urease mutant soybean plants, as well as to analyze the levels of some nitrogen compounds in the leaves. For this, mutant soybean plants of the following genotypes were cultivated: eu1-a, eu3-a, eu4-a, eu1-a/eu4-c, and Williams 82. After reaching the stage of seed and pod formation, the plants were collected and biometric and biochemical analyzes were performed. Regarding the growth parameters, some differences were observed between the genotypes, mainly between eu4-a concerning the others. In the biochemical analyses, only the nitrate content differed between the mutants. In general, we can conclude that there are differences in the growth of mutant and control genotypes and, at first, the Williams 82 control seems to be the most productive. However, we suggest that more studies be done to evaluate the productivity of the mutants.
Productivity in different soybean genotypes for urease enzyme
Keywords: Urease; Ureia; Nitrato; Proteinas; Urease; Urea; Nitrogen; Protein; Nitrate; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL